The impact of youth enterprise development fund on the transition of youth to adulthood in Gatanga Sub-County, Kenya - Wamukoya, Wilkyster (Department of Social Development, 2025)
For the young people to attain adulthood status, there are relevant markers and dimensions of development which are used to measure their transition. The government of Kenya initiated a youth fund program in 2007 to support the youth during this critical stage of transition to adulthood. The contribution of this fund (youth enterprise development fund, YEDF) in facilitating youth transition to adulthood has never been investigated in Kenya. In addition, the researcher did not find any similar studies that have investigated the contribution of funding to youth transition to adulthood elsewhere in the world. The main aim of this research is to investigate the impact of YEDF on the transition of youth to adulthood in Gatanga sub-county, Kenya. The study draws largely from the findings of Arnett through his invention of “emerging adulthood theory” which lays emphasis on factual issues affecting education, marriage and employment which are relevant in studying youth transition to adulthood. The study utilized two measures of transition to adulthood as proposed by Arnett, namely, “Markers of Adulthood” (MoA) and “Inventory of the Dimensions of Emerging Adulthood” (IDEA) scales to assess emerging adulthood related issues to reveal any differences between funded and non-funded youth in Gatanga sub-county. Relevant data were collected using questionnaires through a stratified random sampling procedure. The participants consisted of 108 each for funded and non-funded youth, stratified by gender and area economic status. The statistical analysis of variance (ANOVA) and analysis of covariance (ANCOVA) were conducted using F- test to establish the significance of MoA and IDEA items in relation to YEDF, to detect differences between the funded and non-funded respondents on a specific item. Standardized factor loading was used to rate perception of MoA and IDEA items by the participants while exploratory factor analysis was used to determine unique factor sub-scales for MoA and IDEA in Gatanga sub-county. At a general level, MoA and IDEA items were fairly endorsed by both the funded and the non-funded participants, although actual figures show differences in a number of sub-scales. ANOVA and ANCOVA results show varying differences between funded and non-funded youths on all MoA and IDEA items. Although significant differences were only noted in one MoA item under Independence sub-scale “capable of financially supporting a family”. On the other hand, significant differences were observed in six IDEA items, namely: three items in Identity Exploration sub-scale “time of deciding your own beliefs and values”, “time of learning to think for yourself” and “time of seeking a sense of meanings”; two items under Experimentation/Possibilities sub-scale “time of open choices” and “time of trying out new things”; and one item under Self-Focused sub-scale “time of focusing on yourself”. The differences between funded and non-funded youth were significantly impacted when marriage and personal income were used as correlates for both MoA and IDEA items. Further analysis shows that personal income through YEDF activities has a positive impact on youth transition to adulthood. No significant differences were noted when education and regional level of economic development were used as correlates. This means personal income may not necessarily depend on regional economic development. Results on standardized factor loading show higher loading (≥ .70) under Role Transitions sub-scale for MoA and Identity Exploration sub-scale for IDEA. Results for exploratory factor analysis show four distinct sub-scales for the community under study, corresponding with the four theoretical MoA sub-scales proposed by Arnett. However, there is no perfect correspondence in items in each sub-scale. On the other hand, nine distinct sub-scales were observed in assessment of IDEA variables for the community under study, these differ from the six theoretical IDEA sub-scales. In general, the results of this study show that YEDF plays a big role in impacting youth transitions through “marriage and personal income/employment” but not “education”. The community under study does not consider education as a critical factor for youth transitioning to adulthood. Further research is needed to understand why education is rated too low in this community.